ALGUNOS PECES FOSILES DEL DENOMINADO PATAGONIANO DEL OESTE DE CHUBUT, ARGENTINA (Ameghiniana, 2013)
In this papers the author describes some fishes belonging to the families Engraulidae, Atherinidae and Istiophoridae, which have not been mentioned before as fossils in South America. They come from the so called "Patagoniano continental" of N. W. Chubut, Argentina ? middle Miocene. The existence of anchovies and sailfish at that time, correlated with a warm fauna of the same beds, point to a temperate or warm palaeoclime and waters, similar to recent conditions in South Brazil and Argentine.